2013
DOI: 10.11604/pamj.2013.15.45.2501
|View full text |Cite
|
Sign up to set email alerts
|

Serial pathologic fractures of five long bones on four separate occasions in a patient with primary hyperparathyroidism, challenges of management in a developing country: a case report

Abstract: Multiple pathologic fractures secondary to parathyroid adenoma is rarely recognized and reported in the tropics. Inadequate evaluation causes worsened disability and increased psychological stress. We present a 27-year-old Nigerian male student with recurrent unexplained pathological fractures of the long bones. Primary Hyperparathyroidism was later diagnosed and he benefited from a unilateral parathyroidectomy. Primary hyperparathyroidism secondary to parathyroid adenoma is difficult to diagnose and needs a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This might be particularly useful especially in laboratory/medical settings relying on limited resources, in which PTH determination is difficult or not possible. In this regard the use of the Ca/P ratio for the diagnosis of PHPT can be extended to every clinical and laboratory setting worldwide, including developing countries, reducing health inequalities due to limited access to diagnostic facilities, such as hormone measurements . Thanks to its simplicity, the Ca/P ratio could be useful in clinical settings characterized by large inflow of patients (eg, general practitioner, emergency room, PHPT screening of osteoporotic patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be particularly useful especially in laboratory/medical settings relying on limited resources, in which PTH determination is difficult or not possible. In this regard the use of the Ca/P ratio for the diagnosis of PHPT can be extended to every clinical and laboratory setting worldwide, including developing countries, reducing health inequalities due to limited access to diagnostic facilities, such as hormone measurements . Thanks to its simplicity, the Ca/P ratio could be useful in clinical settings characterized by large inflow of patients (eg, general practitioner, emergency room, PHPT screening of osteoporotic patients).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard the use of the Ca/P ratio for the diagnosis of PHPT can be extended to every clinical and laboratory setting worldwide, including developing countries, reducing health inequalities (40) due to limited access to diagnostic facilities, such as hormone measurements. (41,42) Thanks to its simplicity, the Ca/P ratio could be useful in clinical settings characterized by large inflow of patients (eg, general practitioner, emergency room, PHPT screening of osteoporotic patients). In all these conditions Ca/P may perform very well, allowing cost savings and selecting patients as candidates for second-line diagnostic procedures such as PTH assay and imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of evidence of studies included in this review mostly (17/18) comprise of case series and cohort studies, however one study, number 11 by Olatoke et al , is a single case report, thus representing low quality evidence. Additionally, this study offered no statistical benefit, however this report of only a single case is due to and demonstrates the challenges of FP in this country, which speaks to the aim of this review ( 45 , 61 ).…”
Section: Discussionmentioning
confidence: 75%
“…Combined 99m Tc sestamibi/US use for preoperative localisation has been reported to have a sensitivity of 96%, in keeping with the sensitivity of preoperative localisation from the developing countries in this study ( 58 ). In a single lower middle-income country, Nigeria, Olatoke et al [2013] demonstrated preoperative localisation to be possible, but not feasible, as each 99m Tc sestamibi test required a 250 km journey to access a facility with the necessary equipment ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, patients can present with a mandibular fracture, as reported in a patient with primary hyperparathyroidism. 12 Giant cell epulis and Sagliker syndrome are also possible manifestations. The mandible is more often affected than the maxilla, but bimaxillary manifestation is common as well.…”
Section: Discussionmentioning
confidence: 99%